2014
DOI: 10.1186/1749-8104-9-7
|View full text |Cite
|
Sign up to set email alerts
|

LPHN3, a presynaptic adhesion-GPCR implicated in ADHD, regulates the strength of neocortical layer 2/3 synaptic input to layer 5

Abstract: BackgroundLatrophilins (LPHNs) are a small family of neuronal adhesion-GPCRs originally discovered as receptors for the black widow spider toxin α-latrotoxin. Mutations in LPHN3 have recently been identified as risk factors for attention deficit hyperactivity disorder (ADHD) in humans, but their physiological function has remained elusive. In this study, we tested two hypotheses regarding LPHN3 function: (1) LPHN3 regulates synaptic transmission by modulating probability of release; and (2) LPHN3 controls syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 28 publications
4
82
1
Order By: Relevance
“…Adhesion GPCRs are a growing research field, and several of these receptors have shown an important role in the CNS (Araç et al, 2012a; Langenhan et al, 2013;Strokes and Piao, 2010). For example, the brain-specific angiogenesis inhibitor (BAI) subfamily is involved in the control of synaptogenesis (Duman et al, 2013;Stephenson et al, 2014), whereas the latrophilins have been implicated in the control of synaptic transmission (O'Sullivan et al, 2012;O'Sullivan et al, 2014) and GPR56 is associated with brain development (Jeong et al, 2012;Luo et al, 2011;Singer et al, 2013).…”
Section: Abstract: Neuron Gpcr Nerve Net Synapse Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adhesion GPCRs are a growing research field, and several of these receptors have shown an important role in the CNS (Araç et al, 2012a; Langenhan et al, 2013;Strokes and Piao, 2010). For example, the brain-specific angiogenesis inhibitor (BAI) subfamily is involved in the control of synaptogenesis (Duman et al, 2013;Stephenson et al, 2014), whereas the latrophilins have been implicated in the control of synaptic transmission (O'Sullivan et al, 2012;O'Sullivan et al, 2014) and GPR56 is associated with brain development (Jeong et al, 2012;Luo et al, 2011;Singer et al, 2013).…”
Section: Abstract: Neuron Gpcr Nerve Net Synapse Evolutionmentioning
confidence: 99%
“…In addition, latrophilin-1interacts with the postsynaptic neurexin I-α and -β, forming a trans-synaptic complex and thus modulating synaptic functions (Boucard et al, 2012;O'Sullivan et al, 2014;Südhof, 2001). The brain-specific angiogenesis inhibitor family (BAIs; subfamily VII adhesion GPCRs) members are well characterised for their roles in synaptogenesis, involving regulation of synapses and synaptic density (for a review, see Stephenson et al, 2014).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is tempting to speculate sponge feeding behaviour involves cell-cell communication mediated through a signalling system involving the glutamate family GPCRs and these chemical messengers. Studies in recent years have also begun to reveal the role of adhesion GPCRs in the nervous system (Silva, et al 2011;Boucard, et al 2012;O'Sullivan, et al 2014). In particular, the adhesion subfamily I latrophilins are involved in the development of the synapse and neurotransmission (Silva, et al 2011;Boucard, et al 2012;O'Sullivan, et al 2014).…”
Section: Tnf Ligandmentioning
confidence: 99%
“…Studies in recent years have also begun to reveal the role of adhesion GPCRs in the nervous system (Silva, et al 2011;Boucard, et al 2012;O'Sullivan, et al 2014). In particular, the adhesion subfamily I latrophilins are involved in the development of the synapse and neurotransmission (Silva, et al 2011;Boucard, et al 2012;O'Sullivan, et al 2014). The adhesion family GPCRs have undergone a large expansion in A. queenslandica, yet scarcely anything is known about their roles in sponges (Krishnan, et al 2014).…”
Section: Tnf Ligandmentioning
confidence: 99%